The Impact of Using Thesaurus Program in Microsoft Word Towards Students’ Vocabulary Mastery - Wenny Octaria Tami (Bandar Lampung University (UBL), 2014)
The goal of this thesis was to find out the impact of using thesaurus program in Microsoft word towards students’ vocabulary mastery in grade eight of SMP Wiyatama Bandar Lampung in academic year 2013/2014. Thesaurus program was used to make the students interested in learning English. It was as a media or technology to enrich their vocabulary.Data were collected by incorporating two pre-tests and two post-tests in experimental group and control group. Treatment using Thesaurus program in Microsoft word was administered in experimental group, while control group received traditional teaching. Data analysis was attempted using t-Test for two group design.After giving the tests, analyze the score was the next step to get the result. Result indicated that p-value 1% = 2, 65, 5% = 2, 00, and t-value = 5,46. It means p-value is smaller than t-value. Therefore, it could be inferred that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The conclusion that can be drawn based on the explanation above was: by using thesaurus was more effective than traditional teaching.